Digitization in Cultural Memory Institutions: A Study on Applications for Cultural Heritage Products - Semanur ÖZTEMİZ; Bülent YILMAZ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Studies performed by cultural memory institutions in order to fulll their major functions have reached different aspects and maybe the most important technological effects on those institutions arise through digitalization applications. Digitalization is taken place for the purposes of protecting valuable materials for some reasons, prevent frequently using collections to wear off and enhance access to these materials. These purposes can be gathered under access, protection and restoration titles, and make digitalization inevitable for library, archive and museum collections at the present time. In this study, it's intended to set forth the current situation of digitalization applications of some state owned cultural memory institutions in Turkey and suggest an ideal workow plan for these applications. The research uses descriptive method and applied on state owned cultural memory institutions those have a corner on the market and still performing or have already completed digitalization applications. Findings of the study shows that the digitalization process is performed considerably irrelevant and inadequate for the above mentioned cultural memory institutions.